2018
DOI: 10.1002/app.47157
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior prediction of friction materials for ultrasonic motors using Monte Carlo‐based artificial neural network

Abstract: In this article, the relationship of complexity, diversity, and uncertainty between components and tribological properties of friction materials based on a Monte Carlo-based artificial neural network (MC-ANN) model was predicted precisely. Meanwhile, the grey relational analysis was applied to figure out weight of factors, optimize formulation design, and calculate nonlinear dependency of ingredients. The accuracy of model was studied by comparing experimental and simulated values on the basis of statistical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The formulations of PTFE composites are listed in Table 1 and obtained with our previous method [25][26][27][28].…”
Section: Materials and Preparationmentioning
confidence: 99%
“…The formulations of PTFE composites are listed in Table 1 and obtained with our previous method [25][26][27][28].…”
Section: Materials and Preparationmentioning
confidence: 99%
“…Therefore, MC-ANN, introduced by Li et al exercises the MC approach to estimate the weights of each neuron in a probabilistic manner. 188 A faster and more accurate MC-ANN aids in better non-linear mapping ability and improved fitting effect of samples. The comparison of the workflow of MC-ANN that is featured in the work of Li et al is shown in Fig.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…In the context of variation and volatility of the data, MC-ANN performs better than conventional ANN because it uses repeated random sampling and a variety of transfer functions like sigmoid, polynomial, tanh, and Gauss functions. 188 (ii) Improved bat algorithm (IBA). A meta-heuristic global optimization algorithm, improved bat algorithm (IBA) is based on the echolocation characteristics of the bat.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…A network trained by gradient search and consisting of three hidden layers (15, 10, and 5 neurons) and tan-sigmoid transfer functions between the input and the hidden layers as well as pure linear transfer functions to the output layer was found to deliver the least mean square errors. Li et al [51] applied a Monte Carlo-based ANN to predict the tribological behavior of PTFE resin with aramid pulp, potassium titanate whisker (PTW), mica, copper (Cu) as well as silicon dioxide (SiO 2 ) for ultrasonic motors and compared the performance to a back propagation ANN. The database, an orthogonal table by variation of the composition, was generated from experiments conducted in triplicate on a quasi-static test rig where the specimens were fixed on a dynamic rotor and slid against a phosphor bronze stator at constant speed and load.…”
Section: Thermoplastic Matrix Compositesmentioning
confidence: 99%